Review of experimental procedures and modelling techniques for flow behaviour and their relation to residence time in constructed wetlands. (June 2021) - Stephenson, Ruth; Sheridan, Craig
Highlights: Constructed wetlands are a useful wastewater treatment technology. The hydraulic modelling of constructed wetlands has developed rapidly in the last 2 decades. When choosing a modelling technique, knowing the flow type of the constructed wetland is critical. The different types of tracers used for residence time distribution studies are also reviewed. Recommendations for which technique to use based on research and design requirements are also given. Abstract: Accurate modelling of constructed wetlands is vital for furthering the use of these systems. Constructed wetlands can treat various types of wastewater, including domestic wastewater, agricultural wastewater, industrial and mining wastewater and stormwater runoff. Physical, chemical and biological processes all take place simultaneously to breakdown the contaminants in wastewater, and while the combination of so many processes makes them an effective wastewater treatment system, it can also make the modelling of these systems intricate. The modelling technique used is dependent on the goal of the model, whether it is for design or scientific research. The extent to which contaminants are broken down by these processes is highly dependent on the time the water spends in the system, and this time is dependent on and can be quantified by the understanding of the hydraulic behaviour of the constructed wetland. Tracer studies are the most common way to determine the hydraulic behaviour of the system and the data from these studies can be used in various ways to quantify time in the system. There are three aims of this paper, the first is to give wetland researchers an idea of what hydraulic modelling techniques are available, the second is to indicate the connection between accurate hydraulic modelling and the modelling of kinetic processes, and the third is to guide the researchers in determining which model is best suited for their needs based on research needs and characteristics of the wetland.